![](https://iknow-base.cdn.bcebos.com/lxb/notice.png)
1个回答
展开全部
n=1,左边=1
右边=(1-e^iθ)/(1-e^iθ)=1
成立。
设n=k时成立:
1十e^iθ十e^i2θ十……十e^i(k-1)θ=(1-e^ikθ)/(1-e^iθ)
n=k十1时
1十e^iθ十e^i2θ十……十e^i(k-1)θ十e^ikθ=(1-e^ikθ)/(1-e^iθ)十e^ikθ
=(1-e^ikθ十e^ikθ-e^i(k十1)θ)/(1-e^iθ)
=(1-e^i(k十1)θ)/ (1-e^iθ)
n=k十1时,也成立。
得证。
右边=(1-e^iθ)/(1-e^iθ)=1
成立。
设n=k时成立:
1十e^iθ十e^i2θ十……十e^i(k-1)θ=(1-e^ikθ)/(1-e^iθ)
n=k十1时
1十e^iθ十e^i2θ十……十e^i(k-1)θ十e^ikθ=(1-e^ikθ)/(1-e^iθ)十e^ikθ
=(1-e^ikθ十e^ikθ-e^i(k十1)θ)/(1-e^iθ)
=(1-e^i(k十1)θ)/ (1-e^iθ)
n=k十1时,也成立。
得证。
推荐律师服务:
若未解决您的问题,请您详细描述您的问题,通过百度律临进行免费专业咨询